Katalog Digital Untuk Promosi Tas Wanita Berbasis Augmented Reality - Firdaus Margo Utomo; Rohman Dijaya (Fakultas Teknik Universitas Hamzanwadi, 2023)
In today's era, marketing techniques use brochures, pamphlets, video advertisements, newspapers and word of mouth. This has a deficiency in consumer confidence because it cannot interact directly with the product of interest. A good marketing strategy methodology will influence buyer interest and increase sales traffic. In this case it provides opportunities for MSMEs, especially UD. Creative to increase sales traffic. Business progress can be seen from the marketing sector which continues to increase. MSME entrepreneurs use marketing methods in the form of pamphlets and word of mouth. This affects the lack of increased sales. This application is able to provide experience to potential customers to interact directly with products in Augmented Reality. This application displays 3D objects in real time and sees the shape of the object in detail, so that potential customers have more confidence in the product to be purchased. This application feature can add other objects stored in external storage or in the form of links, so users don't have to bother rebuilding the application when they want to add other objects